Новые виды яйцеедов подрода Anolcus Кiеffеr, 1913 рода Telenomus Hаlidау, 1833 (Proctotrupoidea, Scelionidae) с Дальнего Востока - Козлов, М.А.; Кононова, С.В. (Вестник зоологии, 1977)
New species of Telenomus-Aholcus are described, the identification key of the subgenus Aholcus species is given for the world fauna.